The relationship between theory of mind and emotion regulation in the preschool years. The role of language and gender - Bulgarelli, Daniela; Sala, Maria Nives; Ragaglia, Beatrice; Molina, Paola (Ricerche di Psicologia - Open Access, 2024)
A few studies investigated the relationship between Theory of Mind (ToM) and Emotion Regulation (ER) in preschoolers, mainly using False Belief tasks for assessing ToM, and disappointment procedures for measuring ER. Mixed findings were reported, as some researchers did not find any association and others did. The current study aims at testing the positive correlation between ToM and ER, using different measures, i.e., the comprehensive test ToM Storybooks, which allows for qualitative, quantitative, and total scores, and the narrative story stem procedure SIRE, which returns four scores: Behavioural Strategy, Cognitive Reappraisal, So-cial Support, and Attentional Deployment. Moreover, the study aims at testing the role of receptive vocabulary size (VS) and gender on the relationship between ToM and ER. Sixty-two Italian 3- to 6-year-old children participated. The three ToM scores, VS score, and ER Behavioural Strategy and Cognitive Reappraisal scores were associated with age. Gender differences were only found in ER Behavioural Strategy and Social Support scores. VS was significantly associated with the three ToM scores and with the ER Behavioural Strategy and Cognitive Reappraisal. Partial correlations controlling for age, gender, and VS showed that ToM Qualitative score was associated with ER Cognitive Reappraisal: more complex ToM abilities were associated with ER cognitive strategies.